Executive Committee Minutes 2015-12-10 - Academic Senate:::::::::
Agenda – Approved. Minutes of 11/19/15 – Approved. Chair Report. Revision to Music Concentrations approved for the Senate's consent calendar. Associated Students Report. Revision to Business Administration minor approved for the Senate's consent calendar. President Report. Provost Report. Statewide Senator Report. Vice Chair Report. Revision to Early Childhood Studies Major approved for the Senate's consent calendar. Vice President of Administration and Finance Report. Feedback on Faculty Retreat. Revised Academic Planning, Assessment and Budget Committee Charge approved as business item for the Senate. Vice President of Student Affairs Report. EPC Report. FSAC Report. Senate agenda approved.